THE PLIGHTS OF AFRICAN RESOURCES PATENTING THROUGH THE LENSES OF THE WORLD TRADE ORGANISATION: AN ASSESSMENT OF SOUTH AFRICA’S ROOIBOS TEA’S LABYRITH JOURNEY - Amusan, Lere (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
As much as developing states are blessed with natural resources capable of transforming their economies into a positive direction, the imposed World Trade Organisation’s (WTO) mores continue to relegate them to the status of underdevelopment. The consequences of this on investment, trade and finance in Third World States (TWSs), especially Africa, are disarticulation of the economy, exploitation, disinvestment, unemployment, political instability and unavailability of relevant technology to move TWSs forward, among others. The intention of this paper is to situate the problems of biopiracy in Africa in terms of its associated western international regimes of intellectual property rights (IPRs), geographical indications (GIs), prior informed consent (PIC), and access and sharing benefits (ASB). This gives rise to the politics behind Rooibos (Aspalathus linearis) patenting (a medicinal plant found only in South Africa) by various multinational corporations (MNCs). There is a need for a regional regime such as African Regional Intellectual Property Organisation (ARIPO), on indigenous knowledge (IK) to patent the continental biodiversity resources. This study adopted political economy approach with emphasis on both primary and secondary sources of data collection.